Performance of Pepper Post Harvest Machines - Wahyu Purwanto; Lamhot P. Manalu (PERTETA, 2002)
The purpose of this study was to learn technical performance and financial feasibility of a unit of mechanical post-harvest processing of pepper. The equipment used in such a process is thresher, peeler and dryer. The equipment was tested to learn its technical performances. It was found that the threshing efficiency of the thresher was 98% with a capacity of 269 kg fresh pepper spikes per hour and damaged berries of 5.3%. The peeling efficiency of the peeler was 98% with an optimum capacity (in term of fresh pepper spikes) of 224 kg per hour.The financial analysis showed that a unit of mechanical post-harvest processing of pepper with a capacity of 30,000 kg per year needs an investment of Rp. 82,060,000.00. This investment wi/l give an NPV of Rp. 141,605,144; net BIC of 2.37 and IRR value of 81.33%. An intensive and local specific study must be carried out to get appropriate conclusions of such an analysis.